2019
DOI: 10.1080/15476286.2019.1612693
|View full text |Cite
|
Sign up to set email alerts
|

Feedback regulation of small RNA processing by the cleavage product

Abstract: Many bacterial small RNAs (sRNAs) are processed resulting in variants with roles potentially distinct from the primary sRNAs. In Enterobacteriaceae sRNA GlmZ activates expression of glmS by base-pairing when the levels of glucosamine-6-phosphate (GlcN6P) are low. GlmS synthesizes GlcN6P, which is required for cell envelope biosynthesis. When dispensable, GlmZ is cleaved by RNase E in the base-pairing sequence. Processing requires protein RapZ, which binds GlmZ and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 51 publications
(74 reference statements)
3
16
0
Order By: Relevance
“…Moreover, the low glmY expression level in the ΔrapZ mutant remained unaffected by overproduction of the sRNAs. As deletion or overproduction of GlmY or GlmZ has no impact on RapZ levels (Durica‐Mitic & Görke, ), these results suggested that GlmY and GlmZ counteract activation of QseE/QseF by RapZ.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Moreover, the low glmY expression level in the ΔrapZ mutant remained unaffected by overproduction of the sRNAs. As deletion or overproduction of GlmY or GlmZ has no impact on RapZ levels (Durica‐Mitic & Görke, ), these results suggested that GlmY and GlmZ counteract activation of QseE/QseF by RapZ.…”
Section: Resultsmentioning
confidence: 96%
“…Total RNA was extracted and analyzed by Northern blotting as described recently (Durica‐Mitic & Görke, ). For RNA half‐life determinations, 500 μg/ml rifampicin was added to the cultures when reaching OD 600 = 1.0 and aliquots were harvested at indicated times by pelleting and freezing in liquid nitrogen.…”
Section: Methodsmentioning
confidence: 99%
“…For confirmation, we made use of a previously established RNase E cleavage assay (Göpel et al 2013(Göpel et al , 2016Durica-Mitic and Görke 2019) to analyze activity of the RapZ CTD in vitro. In this assay, correct cleavage of radiolabeled GlmZ yielding the 155 nt long 5 ′ cleavage product (designated GlmZ * ) only occurs in the presence of both RapZ and Rne NTD (Fig.…”
Section: Rna Is Dispensable For Rapz/rnase E Complex Formationmentioning
confidence: 99%
“…Accordingly, we hypothesize that short RNAs adopting G-quadruplex structures may sequester Dicer in vivo. Such a mechanism could be a part of autoregulatory loops, in which Dicer-processed guanine-rich miRNAs, in the form of G-quadruplexes, act in a negative feedback regulation of Dicer [ 17 , 41 ]. The sequestration of Dicer by RNA G-quadruplexes may control the pool of Dicer available for the biogenesis of miRNA.…”
Section: Discussionmentioning
confidence: 99%